2017
DOI: 10.1016/j.ijmedinf.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Prescription errors related to the use of computerized provider order-entry system for pediatric patients

Abstract: Our work revealed several error types in prescribing for pediatric patients, mainly absence of bodyweight, incorrect frequency of administration and excessive doses. Information on bodyweight is crucial in pediatric patients: our study highlights the need to make it mandatory to complete prescriptions via CPOE systems. The role of better software design is pivotal to avoiding these errors. In addition to optimizing the quality of CPOE-entries, well-designed software, better-trained users, and improved communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…The control of medical prescriptions is important. Computational systems, which are already in use in several countries, are helpful, but can still have limitations (Alhanout et al 2017). The control of prescriptions is especially important in the case of older persons, who often take the same active substance supplied by a different specialist.…”
Section: Prescription and Sales Of Pharmaceuticalsmentioning
confidence: 99%
“…The control of medical prescriptions is important. Computational systems, which are already in use in several countries, are helpful, but can still have limitations (Alhanout et al 2017). The control of prescriptions is especially important in the case of older persons, who often take the same active substance supplied by a different specialist.…”
Section: Prescription and Sales Of Pharmaceuticalsmentioning
confidence: 99%
“…Although the use of CPOE is linked to notable improvements in reducing and/ or limiting MEs, others argue that the use of CPOE might facilitate MEs, or CPOE itself could become a source of errors. [14][15][16][17] As an example, a recent study 18 found that nearly 6 percent (63,040) of the MEs reported to MEDMARX-an anonymous, confidential, Internet-accessible, ME-reporting program that is designed and developed by the US Pharmacopeia for hospitals and health systems to systematically collect, analyze, track, and report MEs 19 -between 2003 and 2010 were related to CPOE. Moreover, Amato et al 20 conducted a study to evaluate different CPOE systems at six sites to review potential CPOE-related MEs occurring in the medication ordering phase.…”
Section: Introductionmentioning
confidence: 99%
“…Although the recent medical literature emphasizes the fact that the use of computerized prescription systems can decrease the frequency of prescription errors and iatrogenic adverse events and increase the safety of drug prescriptions, we consider that the system correction algorithm can sometimes generate errors ‐ especially in the setting of rare diseases. Indeed, recent literature on medication errors linked to a computerized physician order entry system emphasized the need to understand and then present the causes of these errors . Since PA is a rare inborn error of metabolism with a small number of patients, some treatments are not referenced and not well known—resulting in medication errors.…”
Section: Discussionmentioning
confidence: 99%